Branding and design - Sinicki, Adam (Apress, 2019)
Create a brand online through the use of web design, graphic design (Illustrator and Photoshop), outsourcing, social media, and various other strategies. The objective of this video is to help you create a coherent design that speaks to the mission statement of the brand, and that will increase audience engagement and loyalty. The main strategy is to create a brand design that is unique to the business and that has a specific buyer persona in mind (not to try and 'appeal to everyone'). This will reference Simon Sinek's 'Golden Circle'. From there, a logo can be designed or outsourced to reflect that mission statement. This should be simple, re-useable, scalable, and non-cliched, and the design process may involve a mood board. The design should be a vector file, and we will look at the technical skills necessary to create such a design. The same branding should then be used through a website, and will help to inform design decisions, as well as across social media. The aim here is 'be everywhere' and 'be consistent'. We will discuss how brand strategy can even influence product design, using Apple as the perfect example. We will also discuss branding in the context of content marketing. What You Will Learn: Create a design aesthetic that expresses your company's valuers and ethos. Choose a mission statement and find a buyer persona to help you meet your goals. Study how you can create and maintain a brand. Who This Video is For: New startups, entrepreneurs, bloggers, and sole traders looking to create a strong platform online. Businesses currently operating with drab and uninspired branding that are losing potential leads as a result.